Control de plagas foliares de la col a base de compuestos orgánicos en la granja Santa Inés - Trujillo Rey, Luis Belisario (2012)
In the Santa Inés Farm of the Universidad Técnica de Machala was make an investigation work about pest foliar control of the cabbage based on organic compounds with insecticides of craft elaboration the same that has the following objectives: 1. Identify the pests of high incidence in the growing, 2. Establish the effectiveness of each treatment, 3. Make an economic analysis about what of the treatments are the most effective. The studied tests were: Garlic to 3 and 5%, Neem to 3 and 5%, Llashipa to 3 and 5%, chili to 3 and 5% and an absolute control. The effectiveness of the treatments was evaluated based on the following variables: Incidence of aphids in establishing growing. 1. Mortality percent of the aphids with garlic extracts, neem, llashipa, chili. 2. Incidence of defoliating pests, evaluation of beneficial insects. 3. Diameter of the cabbage. 4. Length of the cabbage. 5. Weigh of the cabbage. 6. Yield per plot. 7. Yield per hectare. The field registers revealed that the first plague that colonized the growing since the small plants were in the seedbed was the grey plant louse of the cruciferous Brevicory nebrasicae and later the lepidopteran caterpillar family Nonrtuidae (Trichoplusiani and Copitarsissp), causing perforations in the foliage overnight. In the colonies of aphids were found cases of parasitism produced by a wasp of the family Braconidae (Himenoptera). The predominant entomology that colonized the crop in the season from September to January was the plant louse of the cruciferous Brevicorine brasicae and its natural enemies, Lysipllebussp, parasitoids identified by the presence of “momias” Sirphidos larvae, Coccinellidos and Crisopas. The incidence reached the 12, 8% of plants with the presence of colonies of up to 800 adult and pupa stages. The second specie damages the foliage and the terminal bud without get to cabbage form was Trichoplusia ni, which is characterized for its green color and a spiracular white stripe and the generally density of aphids led to the application of two aspersions with the treatments to the third and tenth week of crop age. The natural compound based on 3% of chili represented an available alternative for the control of aphids because it had a high effectiveness that minimizing the population of these insects. In addition this organic compound is economic for the producer’s pocket, friendly to the environment and the health to the people. The pest density does not influence about diameter and the height of the cabbage, but if the yield per plot considering that the damages caused are reflected in crop productivity.